2-Dimethylaminoethanol (Deanol) in Huntington's chorea. Issue 12 (December 1978) - Caraceni, T. A.; Girotti, F.; Celano, I.; Parati, E.; Balboni, L.
Abstract : A double-blind crossover trial with 2-dimethylaminoethanol (Deanol), a possible precursor of brain acetylcholine, was carried out in nine patients with Huntington's chorea. It was found to be ineffective in inducing any alteration in hyperkinesia.